(untitled) (قضايا سياسية, 2022)
This paper introduces a study about the concept of societal security and Egypt’s vision 2030. Furthermore, the paper discusses how Egypt’s vision 2030 seeks to achieve societal security in its modern sense. As the member states of the United Nations have adopted the UN sustainable development goals that were introduced in 2015 and to be achieved by 2030, Egypt’s vision came congruent with the international vision yet, with certain particularity. In 2016, the Egyptian government put forward its strategy for sustainable development under the rubric “Egypt’s vision 2030” to guide Egypt’s trajectory for the next fifteen years. This long term developmental strategy covers political, economic, and environmental domains. However, this strategy faces serious challenges that could impede the achievement of its developmental goals.